PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT ELTAMA PRIMA PERKASA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Alim Malik Lukmanul Hakim; Partogi Saoloan Samosir (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of organizational culture and organizational commitment on job satisfaction through work motivation as a mediating variable. This study was designed as an empirical study to test the hypothesis and was designed as a cross-sectional study. The method used in this research is descriptive analysis method and path analysis. Meanwhile, to test the instrument is done through the validity test and reliability test. The results of the regression analysis show that organizational culture and organizational commitment have a significant effect on work motivation, organizational culture and organizational commitment have a significant effect on employee performance. The results of path analysis show that organizational culture and organizational commitment have an effect on job satisfaction, but different from organizational commitment to job satisfaction, motivation does not provide mediation support.